The synergistic cooperation of NH⋯O and CH⋯O hydrogen bonds in the structures of three new phosphoric triamides. (3rd April 2018) - Saneei, Anahid; Pourayoubi, Mehrdad; Jasinski, Jerry P.; Jenny, Titus A.; Crochet, Aurelien; Fromm, Katharina M.; Keeley, Amanda C.
GRAPHICAL ABSTRACT: ABSTRACT: The supramolecular assemblies of three new phosphoric triamides, {(C6 H5 CH2 )(CH3 )N}2 (4-CH3 -C6 H4 C(O)NH)P(O) (1 ), {(C6 H11 )(CH3 )N}2 (4-CH3 -C6 H4 C(O)NH)P(O) (2 ) and {(C2 H5 )2 N}2 (4-CH3 -C6 H4 C(O)NH)P(O) (3 ) were studied by single crystal X-ray diffraction as well as by Hirshfeld surface analysis. It was found that a synergistic cooperation of NH⋯O and CH⋯O hydrogen bonds occurs in all three structures, but forming unique supramolecular architectures individually. Along with the presence of centrosymmetric dimers in1, 2 and3, based on a classical NH⋯O hydrogen bond, the presence of weak CH⋯O interactions play an additional and vital role in crystal architecture and construction of the final assemblies, collectively identified as a centrosymmetric dimer (0D), a 1-D array and a 3-D network, respectively. These differences in superstructures are related to the effect of aromatic, bulk and flexible groups used in the molecules designed, with a similar C(O)NHP(O) backbone. The NH⋯O contacts in1, 2 and3 are of the "resonance-assisted hydrogen bond" types and also the anti -cooperativity effect can be considered in the multi-acceptor sites P═O in1 and2 and C═O in3 . All three compounds were further studied by 1D NMR experiments, 2D NMR techniques (HMQC and HMBC (H–C correlation)), high resolution ESI–MS, EI–MS spectrometry and IR spectroscopy methods.